International law in crisis: Russia's struggle for recognition - Marxsen, Christian (MPIL research paper series, 2016)
This article discusses the impact of the conflict between Ukraine and Russia on the international legal system, particularly in regard to the prohibition of the use of force. As an initial approach, the paper reflects on the concrete effects of the crisis on the substance of the provisions of the jus contra bellum. Identifying the distinct legal claims put forward by Russia it is argued that the crisis has left the substance of the law untouched. The crucial dimension of the crisis, which is the main claim of the paper, does not lie on the level of substantive legal provisions, but rather concerns the recognition that States express towards each other in international law - a recognition that is, at the same time, required to uphold the normative power of international law. Taking a series of prior violations of international law by Western States into account, the paper argues that we have to interpret the current crisis as a struggle for recognition in which Russia aims to oppose Western instrumental use of international law and to regain its lost political strength. The paper then discusses Russia’s strategies in this struggle for recognition, through which Russia challenges Western reaction patterns and aims to dominate the rules of the conflict. Ultimately, the paper argues that the crisis exemplifies both - the robustness of international law’s substantive provisions and the fragility of international law vis-á-vis short term incentives driven by political power
Gesehen am 27.07.2017